Trends and Inequities in food, energy, protein, fat, and carbohydrate intakes in rural Bangladesh - Ahmed, Akhter; Bakhtiar, M. Mehrab; Ali, Masum; Ghostlaw, Julie; Nguyen, Phuong Hong (Elsevier, 2022)
Background: Tracking dietary changes can inform strategies to improve nutrition, yet there is limited evidence on food consumption patterns and how disparities in food and nutrient intakes have changed in Bangladesh.